2012
DOI: 10.1519/jsc.0b013e318239c3a1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cold Water Immersion on 48-Hour Performance Testing in Collegiate Soccer Players

Abstract: This randomized, controlled, laboratory study was designed to examine the effect of cold water immersion (CWI) as a recovery modality on repeat performance on the yo-yo intermittent recovery test (YIRT), a widely accepted tool for the evaluation of physical performance in soccer, separated by 48 hours. Twenty-two healthy Division I collegiate soccer players (13 men and 9 women; age, 19.8 ± 1.1 years; height, 174.0 ± 9.0 cm; mass, 72.1 ± 9.1 kg) volunteered as participants during the noncompetitive season. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 18 publications
3
28
1
1
Order By: Relevance
“…Of the 21 studies that met all selection criteria, 9 showed only positive average effects of cooling on the recovery of performance. [22][23][24][25][26][27][28][29][30] In 10 studies, mixed (positive and negative) effects on different target parameters were found. [31][32][33][34][35][36][37][38][39][40] In 2 studies, only negative average effects were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 21 studies that met all selection criteria, 9 showed only positive average effects of cooling on the recovery of performance. [22][23][24][25][26][27][28][29][30] In 10 studies, mixed (positive and negative) effects on different target parameters were found. [31][32][33][34][35][36][37][38][39][40] In 2 studies, only negative average effects were observed.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, several studies showing negligible effects did not test performance for periods longer than 48 hours. 27,36,37,42 On the other hand, studies showing large effects for all time frames 28 have more weight on average effect size for time frames including fewer studies in total. Further indications regarding the influence of the time frame might be obtained by looking at the 3 studies that measured performance at several points of time up to at least 96 hours.…”
Section: Timing Of Performance Testingmentioning
confidence: 99%
“…DOMS was always assessed in a squat position (90° knee angle, with brief holding of maximum 3 seconds) ranging from zero (no soreness) to ten (severe soreness), while BORG ratings were always assessed in a standing position 2729…”
Section: Methodsmentioning
confidence: 99%
“…with their out stretched arm. 3,12 Since this test involves an asymmetric vertical reach with one 41 arm, alternative tests have been adopted to better isolate the actual jump performance, and 42 eliminate the reaching component. To this end, CMJ performance has been assessed using 43 contact mats 4,8,11,13,14 or optoelectric systems 1,[5][6][7]9,10 that can accurately measure flight time, and 44 thereby calculate center of mass vertical displacement.…”
Section: Introduction 34 35mentioning
confidence: 99%